Strategies to Reduce Maternal and Child Mortality Rates through "Buaian Services" in East Java - Mustofa, Amirul; Alifa, Rifda (Jurnal Administrasi Publik, 2024)
The Maternal and Child Mortality Rate in the last five years is still considered high, because it is below the national mortality rate. The East Java Provincial Government is trying to reduce this figure through the "buaian service" program in line with increasing economic growth. This study aims to assess the effectiveness of the strategies implemented by the Government of East Java to reduce maternal and child mortality. The theory used to analyze is the theory of reduction strategies which are classified into (1) advocacy programs, (2) social support, and (3) community empowerment. This research employs qualitative methods with interactive analytical techniques. The main focus is on the Government of East Java's efforts to develop new strategies to address the increasing maternal and infant mortality rates. The research occurs at the East Java Health Office and involves condensation, data analysis, verification, and conclusion techniques. The study's findings indicate a decrease in maternal mortality rates attributed to comprehensive support provided by health workers and community health volunteers throughout pregnancy and postpartum. Expectant mothers are hopeful that these maternity services will be able to effectively support and manage high risk pregnancies in East Java with patience and care.